Re‐evaluation of guar gum (E 412) as a food additive. (24th February 2017) - ,; Mortensen, Alicja; Aguilar, Fernando; Crebelli, Riccardo; Di Domenico, Alessandro; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Lambré , Claude; Leblanc, Jean‐Charles; Lindtner, Oliver; et al.
Abstract: The Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of guar gum (E 412) as a food additive. In the EU, guar gum was evaluated by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) in 1970, 1974 and 1975, who allocated an acceptable daily intake (ADI) 'not specified'. Guar gum has been also evaluated by the Scientific Committee for Food (SCF) in 1977 who endorsed the ADI 'not specified' allocated by JECFA. Following the conceptual framework for the risk assessment of certain food additives re‐evaluated under Commission Regulation (EU) No 257/2010, the Panel considered that adequate exposure and toxicity data were available. Guar gum is practically undigested, not absorbed intact, but significantly fermented by enteric bacteria in humans. No adverse effects were reported in subchronic and carcinogenicity studies at the highest dose tested; no concern with respect to the genotoxicity. Oral intake of guar gum was well tolerated in adults. The Panel concluded that there is no need for a numerical ADI for guar gum (E 412), and there is no safety concern for the general population at the refined exposure assessment of guar gum (E 412) as a food additive. The Panel considered that for uses of guar gum in foods intended for infants and young children the occurrence of abdominal discomfort should be monitored and if this effect is observed doses should be identified as a basis for further risk assessment. The Panel considered that no adequate specific studies addressing the safety of use of guar gum (E 412) in food categories 13.1.5.1 and 13.1.5.2 were available. Therefore, the Panel concluded that the available data do not allow an adequate assessment of the safety of guar gum (E 412) in infants and young children consuming these foods for special medical purposes.